2008
DOI: 10.1128/mcb.00393-08
|View full text |Cite
|
Sign up to set email alerts
|

Rap1a Is a Key Regulator of Fibroblast Growth Factor 2-Induced Angiogenesis and Together with Rap1b Controls Human Endothelial Cell Functions

Abstract: Angiogenesis, the formation of new blood vessels from existing vasculature, is regulated primarily by endothelial cell activity. We show herein that the Ras family GTPase Rap1 has a key role in the regulation of angiogenesis by modulating endothelial cell functions. Blood vessel growth into fibroblast growth factor 2 (FGF2)-containing Matrigel plugs was absent from rap1a ؊/؊ mice, and aortic rings derived from rap1a ؊/؊ mice failed to sprout primitive tubes in response to FGF2, when the tissue was embedded in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 57 publications
6
85
0
Order By: Relevance
“…Interestingly, we found that not all cellular events differentially utilized Rap1 isoforms. In agreement with previously published work, 36,42 we observed that loss of either isoform inhibited directed chemotactic migration of ECs Figure 3. characterization of isoform-specific knockdown approach.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Interestingly, we found that not all cellular events differentially utilized Rap1 isoforms. In agreement with previously published work, 36,42 we observed that loss of either isoform inhibited directed chemotactic migration of ECs Figure 3. characterization of isoform-specific knockdown approach.…”
Section: Discussionsupporting
confidence: 82%
“…41 However, in endothelial cells (both microvascular ECs and HUVECs), the consensus seems to be that both isoforms are required for effective migration in wound healing assays, 36,39,42 an observation that our migration data confirms (sup. fig.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…2E). Rapgef1 is involved in regulation of Fgf signaling (37) and its expression implies a unique role in the trophoblast, although Fgf signaling is also involved in some aspects of endothelial development (38). In contrast, Eng, Psen1, Ppap2b, Reck, and Cav1 were all detected uniquely in EC (Fig.…”
Section: Fig 2 Plasma Membrane Markers Of the Blood-tissue Interfacmentioning
confidence: 99%